Gut Microbiota and Short Chain Fatty Acids: Implications in Glucose Homeostasis - Portincasa, Piero; Bonfrate, Leonilde; Vacca, Mirco; De Angelis, Maria; Farella, Ilaria; Lanza, Elisa; Khalil, Mohamad; Wang, David Q.-H.; Sperandio, Markus; Di Ciaula, Agostino (International journal of molecular sciences, 2022)
Gut microbiota encompasses a wide variety of commensal microorganisms consisting of trillions of bacteria, fungi, and viruses. This microbial population coexists in symbiosis with the host, and related metabolites have profound effects on human health. In this respect, gut microbiota plays a pivotal role in the regulation of metabolic, endocrine, and immune functions. Bacterial metabolites include the short chain fatty acids (SCFAs) acetate (C2), propionate (C3), and butyrate (C4), which are the most abundant SCFAs in the human body and the most abundant anions in the colon. SCFAs are made from fermentation of dietary fiber and resistant starch in the gut. They modulate several metabolic pathways and are involved in obesity, insulin resistance, and type 2 diabetes. Thus, diet might influence gut microbiota composition and activity, SCFAs production, and metabolic effects. In this narrative review, we discuss the relevant research focusing on the relationship between gut microbiota, SCFAs, and glucose metabolism.